Ensino-aprendizagem de língua portuguesa e antirracismo: uma proposta dialógica na educação básica. - Sousa, Priscila Gabriela Oliveira (2023)
Inscribed in the dialogical perspective of language, based on Paulo Freire's pedagogical conception, and supported by studies of Indisciplinary Applied Linguistics and his proposal of reflective, ethical and humanist teaching, related to social practices, the general objective of this dissertation was the development of a participatory research (PP) aimed at the 2nd year of high school in a public school in Goiás, aimed at the construction, implementation and evaluation of a didactic unit centered on the anti-racism theme and thus allowing students to appropriate the Critical Racial Literacy discourse, manifesting their positions and occupying a social role of raising awareness, informing and enunciating the importance of the topic. As specific objectives: I sought to identify the students' positions about anti-racism in the activities proposed by me, a teacher-researcher; to analyze the students' perceptions about the didactic unit developed in Portuguese language classes; and understand to what extent aspects related to the elaboration and implementation of the didactic unit contribute to a self-reflective process involving my practice as a teacher-researcher. After the development of the activities, the participants were able to get to know and appropriate the discourse of the LRC, expressing their positions, from posts produced and posted on a social network, occupying a social place of raising awareness, informing and enunciating about the importance of the theme. His sayings resonated with the experiences and dialogues experienced at school, in view of the discussions made possible about the anti-racist theme, through didactics in Portuguese, focused on basic education, capable of illuminating the LRC, giving students the opportunity to enter into dialogues, exploring, for instance, concepts such as structural racism and meritocracy.